1987
DOI: 10.1080/01483918708081882
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High Performance Ion Chromatographic (HPIC) Method for the Determination of Sodium Metabisulfite in Parenteral Formulations

Abstract: A high performance i o n chromatographic (HPIC) method f o r the determination o f sodium m e t a b i s u l f i t e (a pharmaceutical antioxidant) i n i n j e c t a b l e formul a t i o n s i s described. The method i s selective f o r both the s u l f i t e and s u l f a t e ions w i t h a minimum o f sample preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A detailed literature survey for SB revealed that a spectroscopic method is available for the determination of sulfite content in aqueous medium using Ellman’s reagent [ 4 ]. Another method allows for the determination of sodium metabisulfite in parenteral formulations by high performance ion chromatography [ 5 ]. In this technique, the correlation coefficient was found to be less (>0.99), the sample precision value was higher than 6.0 % and the stability-indicating capability of the method was not demonstrated according to ICH guidelines [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed literature survey for SB revealed that a spectroscopic method is available for the determination of sulfite content in aqueous medium using Ellman’s reagent [ 4 ]. Another method allows for the determination of sodium metabisulfite in parenteral formulations by high performance ion chromatography [ 5 ]. In this technique, the correlation coefficient was found to be less (>0.99), the sample precision value was higher than 6.0 % and the stability-indicating capability of the method was not demonstrated according to ICH guidelines [ 6 ].…”
Section: Introductionmentioning
confidence: 99%